2008
DOI: 10.1063/1.2885051
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of electric dipole (hyper)polarizabilities by long-range-correction scheme in density functional theory: A systematic assessment for polydiacetylene and polybutatriene oligomers

Abstract: The long-range correction (LC) for treating electron exchange in density functional theory, combined with the Becke-Lee-Yang-Parr (BLYP) exchange-correlation functional, was used to determine (hyper)polarizabilities of polydiacetylene/polybutatriene oligomers. In comparison with coupled-cluster calculations including single and double excitations as well as a perturbative treatment of triple excitations, our values indicate that the tendency of conventional functionals to result in a catastrophic overshoot for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
69
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(73 citation statements)
references
References 14 publications
4
69
0
Order By: Relevance
“…On this basis our LDA and GGA data give catastrophically exaggerated values (DFT catastrophe), whereas hybrid data are more reasonable but still far apart by orders of magnitude when γ xxxx is considered. LR corrections 52,53 have been claimed, in the case of finite oligomer chains, to limit catastrophic divergence on (hyper)polarizabilities, but still performance depends parametrically on the system 52 and no clear improvements of LR corrected functionals over HF have been shown. 52,53 Besides the wide family of small-gap organic polymers, there is a connection with the optical properties of more complex systems such as carbon nanotubes (CNT) (1D systems characterized by a small band gap).…”
Section: Discussionmentioning
confidence: 99%
“…On this basis our LDA and GGA data give catastrophically exaggerated values (DFT catastrophe), whereas hybrid data are more reasonable but still far apart by orders of magnitude when γ xxxx is considered. LR corrections 52,53 have been claimed, in the case of finite oligomer chains, to limit catastrophic divergence on (hyper)polarizabilities, but still performance depends parametrically on the system 52 and no clear improvements of LR corrected functionals over HF have been shown. 52,53 Besides the wide family of small-gap organic polymers, there is a connection with the optical properties of more complex systems such as carbon nanotubes (CNT) (1D systems characterized by a small band gap).…”
Section: Discussionmentioning
confidence: 99%
“…According to previous studies on (hyper)polarizabilities [24][25][26][27][28][29][30][31], a bigger impact can be expected for larger molecules. More importantly, this work confirms the conclusion of a previous study on excitation energies and oscillator strengths of a few small molecules [46] in that the TDRSH method is a reasonably accurate method even using only a LDA-type density functional and without adding an explicit treatment of long-range correlation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the LC scheme corrects the underestimation of Rydberg excitation energies of small molecules [23] and the overestimation of (hyper)polarizabilities of long conjugated molecules [24][25][26][27][28][29][30][31] usually obtained with standard (semi)local densityfunctional approximations. A variety of other similar range-separated TDDFT schemes have also been employed, which for example use an empirically modified correlation density functional depending on the rangeseparation parameter [32], or introduce a fraction of HF exchange at shorter range as well [33][34][35][36][37][38][39][40][41][42][43][44][45], such as in the CAM-B3LYP approximation [33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, positively large b was reported for a tictoid at twisted angle h ¼ 49 at CASSCF (2,2)/6-31G(d,p) level, whereas b becomes negatively large at h ¼ 53 [44]. On the other hand, DFT methods, in particular to functionals with long-range correction (LC-DFT) to exchange term, are successfully used in evaluating NLO properties for large pextended systems [45][46][47]. We notice that DFT, MP2, and CASSCF produce similar energy variation with twist angle for tictoids [44].…”
mentioning
confidence: 99%